Traps at the hBN/WSe2 interface and their impact on polarity transition in WSe2. (3rd May 2021) - Ali, Fida; Ahmed, Faisal; Taqi, Muhammad; Mitta, Sekhar Babu; Ngo, Tien Dat; Eom, Deok Joon; Watanabe, Kenji; Taniguchi, Takashi; Kim, Hyoungsub; Hwang, Euyheon; Yoo, Won Jong
Abstract: Semiconducting two-dimensional (2D) materials-based devices usually exhibit inferior electrical performance compared to their theoretical predictions, which is mainly attributed to the presence of high density of interfacial defect induced trap states within the bandgap of 2D materials. It is pertinent to control the density of interface traps ( D it ) and identify their respective energy levels inside the band gap of the 2D materials to understand the tailored device performance. Here, we report the large modulation of D it by electrical gating and varying the channel thickness of tungsten diselenide (WSe2 ) placed on ultra-clean hexagonal boron nitride (hBN) gate insulator in a metal–insulator–semiconductor structure, which is revealed by performing multi-frequency capacitance and conductance measurements. Analysis of the 2D hBN/WSe2 interface reveals that with the increase of WSe2 thickness, D it at the midgap of WSe2 is reduced to 6 × 10 9 cm −2 eV −1, which is less than D it reported for SiO2 /Si interface (∼10 10 cm −2 eV −1 ). Furthermore, by increasing thickness and applying gate voltage, D it distribution is systematically modulated inside the WSe2 band gap from valence band edge to mid-gap to conduction band edge, thereby changing the Fermi level of WSe2, and inducing versatile device polarity. Our results show that D it and its spatial energy distribution within the thickness tailored WSe2 band gap primarily control polarity modulation in WSe2 .